INDEXADORES DE QUALIDADE FISICA DE UM ARGISSOLO VERMELHO SUBMETIDO A DIFERENTES SISTEMAS DE MANEJO NO CERRADO - HENRIQUE, Elianay da Cruz; SANTOS, Wesley Vieira; MARTINS, Jennifer Caroline Vilalba; NASCIMENTO, Maryanne Ramos; MENEZES, Roniedison da Silva; PANACHUKI, Eloi (ANAIS DO ENIC, 2024)
-